Mitigating disergonomic risks: manual manipulation of metallic structures for electric power transmission lines - Arteaga-Irene, Yober Jenry (2024)
Electricity is a fundamental commodity for society. However, the installation and assembly of infrastructure for its generation and distribution pose intricate ergonomic challenges for workers. In this context, the study aimed to evaluate and mitigate disergonomic risks related to the activities of loading and unloading metallic structures for electrical transmission lines. Initially, the research identified discomfort zones using the Corlett and Bishop diagram, followed by the classification of postures through the REBA method. Subsequently, risk levels were quantified using Ergonautas software, and finally, improvement actions were formulated and implemented to mitigate the identified risks. The results revealed prevalent discomfort in the lumbar, dorsal, and right foot regions. Additionally, the intervention measures reported a significant reduction in “very high”, “high”, and “medium” risk levels by 44 %, 7 %, and 6 %, respectively.